(3bUU GdCfHjGAs - (3GdcSGFj, Ydj Hf MeRI Hf YHO Gddg, J (B189 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CHh eMSf Hf YHO Gddg GdcSGFj GdMeO ddg GdPj CfHJ GdNdb fHGJG hLYdge CMjGA gPG cJGH LeYJ ajg GdeHJOBJ aj Ndb GdSehGJ hGdCQV hNdb GdLf hGdEfS s
(3BNQgG (B:s
(3GdXGgQI GdeGd hGdKQhI hGdHGWfI GdYde hGdMceI (B, (3GdXGgQI MaX GdbQBf hGdHGWfI age (B( ) (3eMce GdbQBf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 283s
(3eYLe GdeDdajf (B2 / 436s
(3cTa GdXfhf (B2 / 1328s
(3gOjI GdYGQajf (B1 / 668s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs